REDUPNYA GEMERLAP PARIJS VAN JAVA, DARI JAARBEURS KE PAMERAN INDUSTRI JAWA BARAT 1920-1964 - , Hafsah Wisananingrum, S.S. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research aims at describing the reproduction of yearly exhibition symbols in Bandung that changed after the declaration of independence. Jaarbeurs was a yearly exhibition held by Netherlandâs government. It was a symbol of Bandung City in terms both of its buildings and its activities. Jaarbeurs took place in Bandung from 1920 to 1941 and it gave a great contribution to present new tradition especially for the al people in Bandung. As the time went by the tradition kept existed in Bandung. However in independence era, this yearly exhibition continued with a changing context ruled by a new regime. There was a reproduction of the activities but the buildings were not reproduced. The activities of the exhibition changed while the buildings had different function.